The Relationship between The Quality of Performing Obligatory Prayers and Student Behavior in Daily Life - Juwita, Vera Angliani; Purnama, Chandra Yudistira (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
Prayer (salat) is a mandatory act of worship for Muslims and plays a key role in shaping daily behavior. This exploratory study aims to examine the relationship between the quality of obligatory prayer, measured through discipline and devotion, and college student behavior. A quantitative survey was conducted with 159 respondents (mean age = 19.7 years), selected using accidental sampling. Data were collected via printed questionnaires. The KMO value for the prayer quality scale was 0.505 (sig. 0.00), with component matrix values ranging from 0.573 to 0.809, and reliability α = 0.665. Results showed significant correlations ( = 0.001–0.018) between the quality of obligatory prayer and various behavioral aspects: self-attitude, relationships with parents, academic behavior, self-control, and social behavior. Parental reminders remain crucial, while higher education level of parents and reduced supervision tend to lower prayer quality. These findings highlight that the quality of obligatory prayer can strengthen self-management and adaptive behavior in college students.